On estimating the Bernoulli regression function using Bernstein polynomials. Issue 17 (9th August 2021) - Babilua, P. K.; Nadaraya, E. A.
Abstract: The estimate for the Bernoulli regression function is constructed using the Bernstein polynomial. The question of its consistency and asymptotic normality is studied. Testing hypothesis is constructed on the form of the Bernoulli regression function. Also, the test is constructed for the hypothesis on the equality Bernoulli functions. The question of consistency of the constructed tests is studied.